The Use of Screw at the Fracture Level in the Treatment of Thoracolumbar Burst Fractures - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2009)
Study Design: In this prospective randomized study, the results of treating unstable thoracolumbar burst fractures by pedicle instrumentation with and without fracture level screw combination were given. Objective: Our aim was to evaluate the efficacy of fracture level screw combination in achieving and maintaining correction in the treatment of unstable thoracolumbar burst fractures. Summary of Background Data: Most authors reported that intraoperative correction of sagittal deformity is important for the maintenance of fracture reduction and is one of the most consistent predictor of satisfactory functional outcome. Methods: Seventy-two patients with unstable thoracolumbar burst fractures were randomized into 4 groups with equal number of patients. In group 1, patients were treated by segmental posterior instrumentation with 2 levels above and 2 levels below the fracture level fixation, in group 2 they were treated as in group 1 with fracture level screw incorporation. In group 3, patients were treated by short-segment posterior instrumentation with 1 level above and 1 level below, in group 4 they were treated by short-segment posterior instrumentation with fracture level screw incorporation. Clinical and radiologic parameters were evaluated before surgery, after surgery, and at follow-up. Results: The average follow-up was 50 months. Fracture level screw combination provided better intraoperative correction and maintenance in the treatment of unstable thoracolumbar burst fractures, which was more prevalent in short-segment fixation group. Conclusions: Reinforcement with fracture level screw combination can help to provide better kyphosis correction and offers immediate spinal stability in patients with thoracolumbar burst fracture.
Keywords: fracture level; screw fixation; kyphosis reduction; SHORT-SEGMENT FIXATION; SPINE FRACTURES; LUMBAR SPINE; UNSTABLE THORACOLUMBAR; POSTERIOR FIXATION; PEDICLE FIXATION; INSTRUMENTATION; FUSION; CLASSIFICATION; STABILIZATION